Confessions of a bitter secret Santa - Bergen, Lara. (New York : Scholastic, 2008)
Noel thinks Christmas can't get any worse when her parents say she won't be taking a vacation. Then the teacher announces a class secret Santa drawing, and who does Noel get? A stuck-up new girl she barely knows! And who does her BFF get? Noel's secret crush! And Noel's own secret Santa is the lamest one ever! Now Noel has visions of Scrooge, not sugar plums, in her head.
"Candy apple."
4.
008-012.
Keywords: Christmas stories; Middle school students -- Juvenile fiction